Beyond Gratification:The Benefits of Pornography and the Demedicalization of Female Sexuality - Jeneanne Orlowski (The Modern American, 2012)
This Paper argues that non-obscene adult pornography should remain protected by the United States Constitution because it has contributed to the demedicalization of female sexuality. There is an ongoing debate among feminists regarding the value of pornography and whether it should be protected under the First Amendment. This Paper explains the background of the debate regarding the status of pornography as a form of speech and whether it has value that warrants its protection. Specifically, this Paper focuses on the removal of nymphomania from the Diagnostic and Statistical Manual and its absence as a modern medical diagnosis as an example of the demedicalization of female sexuality. The demedicalization of female sexuality has positively affected women in the United States. Catalysts for this demedicalization include the production and consumption of adult pornography by women. For this reason, adult pornography deserves continued protection as a form of free speech under the First Amendment.
Keywords: amériques; corps; cours; discipline; droit; droits des femmes*; premier cycle; régions géographiques; santé; science politique et droit; sex1911; sexualité; sofia; thématiques; états-unis